Pengaruh Nilai-nilai Sosial, Lingkungan Kerja, Personalitas, Pertimbangan Pasar Kerja, dan Pengaruh Orang Tua Terhadap Proses Pemilihan Karir Mahasiswa Akuntansi sebagai Akuntan Publik (Studi Kasus pada Mahasiswa S1 Jurusan Akuntansi Universitas Brawijaya) - I Wayan Budi Darmawan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The objective of this research is to assess the influence of social values, working environment, personality, workforce market consideration, and parental influence on the choice of accounting students to work as public accountant. The sample of this study is 285 accounting students of Faculty of Economics and business of Brawijaya University from classes of 2013, 2014, and 2015. The data of this study are collected through questionnaires and analyzed using logistic regression. The result of the analysis shows that personality influences students’ career option to work as public accountant, while social values, working environment, workforce market consideration, and parental do not influence it. The implications of this research are to provide views to students in choosing a career and to educational institution in lectures process or in the process of career counseling.Keywords: career, social values, working environment, personality, workforce market consideration, parental influence, public accountant